2006
DOI: 10.1177/0886260506293484
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Help-Seeking From Informal Networks Among African American Victims of Intimate Partner Violence

Abstract: The purpose of this study was to gain an understanding of the challenges African-American women in abusive relationships face when they consider seeking-help from their informal networks. Data are reported from interviews with 15 African-American women who were self-identified as having survived physical intimate partner violence. A 13-item, semi-structured interview guide was developed in order to elicit information from participants. All of the interviews were audio-recorded, transcribed, and coded for analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
98
0
4

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(111 citation statements)
references
References 16 publications
2
98
0
4
Order By: Relevance
“…Research in Western settings often is inapplicable because it has focused on women's help seeking from formal institutions (e.g., Abu-Ras 2007;Bonomi et al 2006;Fugate et al 2005;Gracia et al 2008;Moe 2007). Research in the West that has focused on women's social relations has revealed supportive and deleterious effects (Brabeck and Guzmán 2008;Goodkind et al 2003Goodkind et al , 2005Ingram 2007;Moe 2007;Morrison et al 2006). In many places, the family has been depicted as a site of unequal power relations, reinforcing gender norms and women's vulnerability to violence (Agoff et al 2007;Hadeed and El-Bassel 2006;Komter 1989).…”
Section: Introductionmentioning
confidence: 95%
“…Research in Western settings often is inapplicable because it has focused on women's help seeking from formal institutions (e.g., Abu-Ras 2007;Bonomi et al 2006;Fugate et al 2005;Gracia et al 2008;Moe 2007). Research in the West that has focused on women's social relations has revealed supportive and deleterious effects (Brabeck and Guzmán 2008;Goodkind et al 2003Goodkind et al , 2005Ingram 2007;Moe 2007;Morrison et al 2006). In many places, the family has been depicted as a site of unequal power relations, reinforcing gender norms and women's vulnerability to violence (Agoff et al 2007;Hadeed and El-Bassel 2006;Komter 1989).…”
Section: Introductionmentioning
confidence: 95%
“…However, there is limited information on disclosure experiences among African American women (for examples see: Amar, 2008; Neville & Pugh, 1997). Additionally, most research has been limited to studies focused on physical and/or sexual IPV with no attention given to the continuum of sexual coercion (Morrison, Luchok, Richter, & Parra-Medina, 2006). The lack of research on disclosure after sexual coercion among African American women is especially troubling because previous research on disclosure and help-seeking following experiences of IPV found that African American women were significantly less likely to seek help from medical professionals than white women (Flicker et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…19 In other settings outside Africa, women's preferences for screening have been attributed to a number of factors including, shame, fear of retaliation from the husband's relatives and an increased risk for divorce in case the husband finds out. 20,21,22,23,24 Furthermore, the protection of family honour, and the possible economic and emotional dependence of women on their husbands may further impact on disclosure and thereby on preference for screening amongst women. 20,25,26 Although the role of some sociodemographic variables (e.g.…”
Section: Introduction Settingmentioning
confidence: 99%